The crystal structure of (1S,3R)-1-(4-isopropylphenyl)-3-(methoxycarbonyl)-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indol-2-iumchloride monohydrate, C22H27ClN2O3 - Zhang Jingxiao; Gu Miao; Bai Xinyu (Zeitschrift für Kristallographie - New Crystal Structures)
C22H27ClN2O3, orthorhombic, P212121 (no. 19), a = 8.6797(3) Å, b = 9.8809(3) Å, c = 24.7824(8) Å, V = 2125.42(12) Å3, Z = 4, Rgt(F) = 0.0478, wRref(F2) = 0.1082, T = 170 K.